Pengaruh Manajemen Keuangan Daerah Terhadap Transparansi Dan Akuntabilitas Pengelolaan Keuangan Daerah Di Indonesia - Ningsih, Kartika Shara; Frinaldi, Aldri; Asnil, Asnil (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Regional financial management is so important for government officials in the regions because it is a logical consequence from the perspective of management of the balance between central and regional finance. The Law also states that regional financial management must adhere to general principles, namely that it must be carried out in compliance with the regulations of the laws that have been made, economically, efficiently, effectively, transparently and responsibly with due observance of the principles of benefit to society and justice. However, events that have occurred will cause various problems that arise due to errors in the management of regional financial management that are not good, such as the use of allocated funds or spending funds that are budgeted or used inappropriately, budgets that are not absorbed optimally and a sense of responsibility for their use. irrelevant budgets that cause people's rights in various regions to not be fulfilled properly in several regions in Indonesia. Based on the results of the research that has been done, it can be concluded that regional financial management influences the transparency and accountability of regional financial management in Indonesia. The success of regional financial management has a direct impact on the success of regional autonomy and a large contribution to realizing good governance. The application of various existing laws and regulations related to the implementation of the concept of accountability and transparency in regional financial management is expected to create good management and side with the people.